Estimating Bathurst Island Peary Caribou and Muskox Populations - Miller, Frank L. (ARCTIC, 1991)
Peary caribou (Rangifer tarandus pearyi) and muskox (Ovibos moschatus) numbers were estimated by systematic aerial survey on Bathurst Island and Bathurst's five western major satellite islands of Vanier, Cameron, Alexander, Massey and Marc, Northwest Territories, in 1985 and 1988. The surveys were carried out as part of the Canadian Wildlife Service's most recent evaluation of the status of Peary caribou (1984-88). In July 1985, 727 Peary caribou and 547 muskoxen were estimated on the six-island survey area and in July 1988, 1034 Peary caribou and 522 muskoxen. Post-parturient caribou cows and their newborn calves occurred at significantly greater rates on Massey Island than on the remainder of the survey area in both years. The 1985 and 1988 survey results, plus results from earlier surveys within the area, are used to illustrate how annual inter-island variation in range use within the survey area by varying numbers of caribou could confound population estimates based on aerial surveys of only Bathurst Island that do not also include, at least, the five western major satellite islands.Key words: Peary caribou, Rangifer tarandus pearyi, muskoxen, Ovibos moschatus, population estimates, inter-island movements, Canadian High Arctic, south-central Queen Elizabeth Islands Mots clés: caribou de Peary, Rangifer tarandus pearyi, boeuf musqué, Ovibos moschatus, estimations de population, mouvements de population entre les îles, Extreme-Arctique canadien, îles centre-sud de la Reine-Élisabeth